Influence of climate on the human species and its relations with physical education in tropical countries (Fiep Bulletin - online, 2015)
Hipecrates, the most  remarkable physician of Ancient Times and a great thinker, considered climate as an assemblage of physical circumstances, proper to each place and related to living beings.